A INTEGRAÇÃO ORIENTE-OCIDENTE E OS FUNDAMENTOS DO JUDÔ EDUCATIVO - Santos, Sérgio Oliveira dos (2013)
Developed in 1882 by Jigoro Kano from his studies of schools of jujutsu, Kodokan Judo arose within the school environment from three basic pillars: as a method of fighting (martial art), as a method of physical training (physical education), as a method of mental training (moral and intellectual development) where Do (path) is the main focus to be taught in order to benefit the society. One of the main contributions of Kano was the transformation of the practice of martial art in an educational method. This process took place in a historical moment marked by social changes in Japan that started receiving strong influence of the Western World during the Meiji era. At that time, the values , thoughts, institutions, and Eastern and Western Languages circulated and merged marking a strong syncretism in different social environments. Would Jigoro Kano have absorbed these influences to develop Judo? This possible link among Eastern and Western Countries, preserving part of traditional Japanese Culture and allowing the influence of Western thoughts and practice, possesses extremely relevance currently as much talked about returning formulations that gave origin to Judo. After all, which formulations are these and how far should we adopt them without further consideration? In the course of the History and more precisely at the end of the 2nd World War, Judo has lost much of the concepts and fundamentals that make the connection with the Language and Eastern thought as well as its original and unique Educational meaning due to its expanding WorldWide as Sports practice. Thus, the study aims to: 1 ) identify the fundamentals of Judo under the influence of the Educational process of the Eastern-Western integration , 2) analyze the relationship of the Eastern Western World during the transformation of Judo Educational method for Sports practice , 3) Organize structuring elements to establish the fundamentals of Contemporary Educational Judo analyzing the influence of the Eastern-Western integration in this process , starting from the systemic model of thought of Jigoro Kano when designing the Judo Kodokan rearranging their conceptual frameworks from the Science of Human Kinetics . This is a theorical study, of bibliographical purpose, which appropriates to the Philosophical Anthropology as a methodological support. The survey results affirm the integration process in the Eastern-Western formulation of the Educational / Philosophical concepts of Judo beyond the transformations of symbolical systems that link the fight of Anthropological - Philosophical Evolution, since the practice of Bujutsu (Military Art, 17th Century) in Medieval Japan, to the Contemporary Educational perspectives supported in Human Motricity Science (HMS).